Supply Chain Finance Application for Improving the Economic Status of the Small and Medium Sized Enterprises - Sturc, B. J; Gurova, T. I. (International Journal of Supply Chain Management, 2020)
In the current highly competitive and fast-changing business environment, in which the optimization of all resources matters, creating an efficient supply chain is crucial. The article examines supply chain finance in economic environment for small and medium sized enterprises (SMEs). This article discusses the main aspects of supply chain finance. The authors describe various theories presented in the works of researchers in this area of financial learning. The issues of making financial decisions, the possible behavior of investors and the external and internal influence of various factors in the process of making these decisions are raised. The article notes that in modern finance, traditional methods of analysis and forecasting do not give a full explanation of the studied financial events. In this regard, when formulating conclusions and summarizing the final calculations, financiers are increasingly talking about the need to study the supply chain finance factors that underlie financial decision-making.